The effect of liquefaction on mineral breakage physical in the Palu City, Central Sulawesi Province, Indonesia. Issue 1 (1st January 2023) - Umar, H; Irfan, U R; Sahabuddin; Cakrawala, M S
Abstract: The Central Sulawesi province had a 7.4 magnitude earthquake in 2018, which was followed by liquefaction in Palu City, Donggala Regency, Sigi Regency, and Parigi Moutong Regency. The boulder sediments, sand, silt, and clay make up the liquefaction material. The extent of mineral damage, mineral surface area, porosity, and sand permeability were all evaluated in this study. By digging a 1 x 1 x 2 m trench at 27 sites, a vertical sampling of liquefaction material was done in both liquefaction-affected and unaffected areas. Smear slides for petrographic investigation were created after the separation of grain sizes. Quartz, biotite, orthoclase, hornblende, plagioclase, and opaque minerals were among the minerals found. Mineral area values in the liquefaction area are lower than in the unaffected area. The Petobo liquefaction area has the highest value of mineral damage, followed by Balaroa, while Sibalaya has the lowest value. In the liquefaction area, where quartz and opaque minerals are less damaged than other minerals, the percentage of mineral damage exceeds 40%. A factor in the deterioration in the carrying capacity of residential land is liquefaction, which causes significant mineral damage but little change in the value of the mineral area. It is suggested that the Petobo and Balaroa areas be designated as green spaces and water catchment areas, while the Sibalaya area can be repurposed as a set of regulated and constrained residential communities.